2017
DOI: 10.1111/jgs.14739
|View full text |Cite
|
Sign up to set email alerts
|

Life‐Space Assessment Predicts Hospital Readmission in Home‐Limited Adults

Abstract: Baseline restricted life-space was associated with greater risk of hospital readmission within 90 days after hospital discharge. These findings suggest a need to customize the management of individuals hospitalized with CHF or COPD based on baseline life-space level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
(73 reference statements)
0
22
0
Order By: Relevance
“…In a study examining whether LSA predicts hospital readmission in patients with COPD or congestive heart failure, Fathi et al 69 reported that unrestricted LSA scores at baseline were associated with greater risk of mobility decline post-discharge compared to restricted LSA at baseline, after controlling for all covariates. Also, restricted LSA before hospitalization was associated with a greater risk of hospital readmission within 90 days of discharge, after controlling for all covariates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study examining whether LSA predicts hospital readmission in patients with COPD or congestive heart failure, Fathi et al 69 reported that unrestricted LSA scores at baseline were associated with greater risk of mobility decline post-discharge compared to restricted LSA at baseline, after controlling for all covariates. Also, restricted LSA before hospitalization was associated with a greater risk of hospital readmission within 90 days of discharge, after controlling for all covariates.…”
Section: Resultsmentioning
confidence: 99%
“…LSM has been found to be a predictor of cognitive decline over 4-years 68 and 5-years 77 of follow-up, 90-day hospital readmission, 69 exacerbations of COPD requiring emergency room and hospital admission, 18 , 84 falls over 8.5 years, 73 mortality, 21 , 72 , 74 , 75 quality of life, 75 , 85 and admission to a nursing home. 76 Findings of this narrative review has shown that LSM instruments can help investigators and clinicians to assess both the current and future mobility status of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The LSA is a well-validated tool that measures how much a person moves in the community, maintains social relationships and roles, exploits community amenities, and participates in meaningful activities (12,13). LSA scores have been shown to predict multiple adverse outcomes (e.g., falls, nursing home admissions, mortality) in community-dwelling older adults (16)(17)(18)(19)(20)(21)(22). Previous studies have demonstrated that declining life-space mobility is associated with lower quality of life (23).…”
Section: The Impact Of Frailty On the Relationship Between Life-spacementioning
confidence: 99%
“…Restricted life-space mobility is associated with various risk factors among older people, declining cognitive function 1) and quality of life 2) , hospital readmission 3) , nursing home admission 4) , and mortality 5) . Baker et al reported that life-space mobility can be evaluated using the Life-Space Assessment (LSA) tool 6) .…”
Section: Introductionmentioning
confidence: 99%